A Semiotic Analysis of Caricatures Depicting Israel – Palestine Conflict on Twiter - Sidabutar, Johannes E; Manik, Sondang; Sembiring, Ronny A (English Lecturers and Teachers Association (ELTA), 2025)
This study discussed Semiotic Analysis Of Caricatures Depicting The Israel-Palestine Conflict On Twitter. This study aimed to identify and analyze icons, indexes, and symbols and find the meaning of their interpretation contained in the caricature. This study uses a qualitative descriptive method using the semiotic theory proposed by Charles Sanders Pierce. In this study, the writer took 20 images via Twitter. Then, the writer described and analyzed the meaning of each sign in the conflict caricature using Pierce's triangle. In this study, the writer found a total of 164 signs in the Israeli-Palestinian conflict caricature on Twitter, consisting of 55 icon data, 50 index data, and 59 symbol data, which reflect the themes of military aggression, civilian suffering, and political influence. This study highlights the role of influential visual media in shaping public perception and political discourse. The findings indicate that symbol signs are the type of signs most often found by the writer in this study. Keywords : Semiotic Analysis; Charles Sanders Pierce theory; Twitter